#T1DLooksLikeMe: Exploring Self-Disclosure, Social Support, and Type 1 Diabetes on Instagram - Holtz, Bree E.; Kanthawala, Shaheen (Frontiers in Communication, 2020)
Type 1 diabetes (T1D) is diagnosed mostly during childhood or adolescent years. During such transitional phases of life, having support from others in similar situations can reduce feelings of isolation and loneliness. Instagram, a platform with high use among teens or young adults, acts as an alternative to traditional online health communities. To better understand individuals self-disclosure on Instagram related to T1D, we conducted an exploratory quantitative content analysis of a sample of 423 posts using the hashtag #t1dlookslikeme. These posts were collected using Netlytic between July – October 2018. Our research questions asked about the types of hashtags used, the content of the images, the sentiments of the posts, the relationship between post engagement and post sentiment, if and how the posts represented self-disclosure, and the presence of social support. A codebook containing 43 items on the image and 10 codes for captions was created for this study, and all data were analyzed using SPSS. Our dataset included 89% images compared to 6.4% video clips. Additionally, 83.5% of the posts were personal images whereas 11.6% were categorized as memes. We noted the most popular hashtags, and other characteristics of the images used by individuals to self-disclose their T1D. Overall, our random sample contained more positive sentiment posts rather than negative – and these positive sentiment posts were correlated with a higher number of hashtags in each post. Indicating a possible connection between self-disclosure and positive sentiment. This finding also reflected elements of empowerment (such as taking the “power” away from T1D and returning it to themselves), which is also discussed.